NECESSITY OF INTELLECTUAL MOBILITY FORMATION AS A BACKGROUND OF PROFESSIONAL SELF-ACTUALISATION OF A TECHNICAL HIGHER EDUCATIONAL ESTABLISHMENT’S TEACHER - Абсалямова, Я. В. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2015)
In the article the essence and importance of professional self-actualization process of the teacher of technical higher educational establishment are explained. The definition of professional self-actualization of the teacher of higher educational establishment is given by author. The necessity of professional mobility formation as a background of his professional self-actualisation is proved. Particularly, the role of intellectual mobility in professional self-actualisation of a technical higher educational establishment’s teacher is stressed. The directions for further studies of the problem are defined